Numerical simulation of a greenhouse coffee drying system using a continuous flow of hot air - Casas, Jose A. (2022)
This paper presents the development and validation of a Coffee Bean Drying System that corresponds to the capacities and needs of small coffee farmers in Peru, which are specifically harvested in regions greater than 800 meters above sea level. This dryer utilizes hot air, which will be introduced into the drying area by a fan, it will be heated using electrical resistances thanks to the principle of Convection, and a new air distribution system will homogenize the flow and speed of the hot air to which the trays filled with coffee beans will be exposed. The coffee beans will enter with an approximate humidity of 50% and will leave the drying chamber with a degree of humidity between the range of 11% to 13%. The thermodynamic analysis of the system was carried out using Computational Fluids Dynamic (CFD) through the ANSYS program, obtaining as a result the validation of the geometry and effectiveness of the hot air distribution system in the dryer, and concluding that the implementation of said element in the system will correspond to an increase in the total efficiency of the Coffee Dryer once implemented.